2016
DOI: 10.1021/acs.jced.6b00563
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of the Pure Deep Eutectic Solvent, [ChCl]:[Lev] (1:2) DES, and Its Binary Mixtures with Alcohols

Abstract: [ChCl]:[Lev] (1:2) DES was synthesized in the laboratory with choline chloride, and levulinic acid, in a 1:2 relationship, stirring both components at 333.15 K and at 101.3 kPa. A thermophysical study of the pure [ChCl]:[Lev] (1:2) DES was realized. Densities, speeds of sound, dynamic viscosities, and refractive indices of the pure [ChCl]:[Lev] (1:2) DES are measured in the temperature range (293.15–343.15 K) and at 101.3 kPa of pressure. Density and refractive index data were additionally used to calculate ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…In order to develop the GC and AC models, the most up-to-date databanks of various types of DESs were collected from the literature. The databanks involved 1239 data points from 149 DESs for density 35 66 , 1117 data points from 142 DESs for refractive index 11 , 39 , 41 43 , 47 , 50 , 54 , 57 , 59 , 63 , 64 , 67 87 , 461 data points from 24 DESs for heat capacity 59 , 70 , 88 93 , 398 data points from 37 DESs for speed of sound 42 , 43 , 67 , 72 , 75 , 77 , 82 , 94 100 and 538 data points from 98 DESs for surface tension 47 , 63 , 71 , 80 , 86 , 87 , 101 – 116 . All of the data were at atmospheric pressure.…”
Section: Methodsmentioning
confidence: 99%
“…In order to develop the GC and AC models, the most up-to-date databanks of various types of DESs were collected from the literature. The databanks involved 1239 data points from 149 DESs for density 35 66 , 1117 data points from 142 DESs for refractive index 11 , 39 , 41 43 , 47 , 50 , 54 , 57 , 59 , 63 , 64 , 67 87 , 461 data points from 24 DESs for heat capacity 59 , 70 , 88 93 , 398 data points from 37 DESs for speed of sound 42 , 43 , 67 , 72 , 75 , 77 , 82 , 94 100 and 538 data points from 98 DESs for surface tension 47 , 63 , 71 , 80 , 86 , 87 , 101 – 116 . All of the data were at atmospheric pressure.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, 420 speed of sound data were collected from literature references, covering 39 different DESs [21,[30][31][32][33][34][35][36][37][38][39][40][41][42]. Table 1 lists these 39 DESs, including their corresponding HBAs, HBDs and molar ratios.…”
Section: Selected Deep Eutectic Solvents (Dess) and Experimental Datamentioning
confidence: 99%
“…Research on viscosity and conductivity of DESs is also inevitable. Sas et al [35] measured the viscosity of DES formed with ChCl and levulinic acid, and it was found that the viscosity of DES obeyed the Arrhenius equation. Moreover, the conductivity of DES was related to its viscosity.…”
Section: Deep Eutectic Solventmentioning
confidence: 99%